Length–weight relationships of eleven mesopelagic fishes from oceanic islands of the Southwestern Tropical Atlantic. (25th November 2018) - Eduardo, Leandro N.; Mincarone, Michael M.; Villarins, Bárbara T.; Frédou, Thierry; Lira, Alex S.; Bertrand, Arnaud; Lucena-Frédou, Flávia
Summary: This study provides the length‐weight relationship for eleven mesopelagic fishes from oceanic islands of the Southwestern Tropical Atlantic: Bonapartia pedaliota, Sigmops elongatus (Gonostomatidae), Argyropelecus aculeatus, Argyropelecus affinis, Argyropelecus sladeni, Sternoptyx diaphana, Sternoptyx pseudobscura (Sternoptychidae), Malacosteus niger, Thysanactis dentex (Stomiidae), Melanonus zugmayeri (Melanonidae), and Ectreposebastes imus (Setarchidae). Data were collected during a scientific survey (2017) around Rocas Atoll, Fernando de Noronha Archipelago and adjacent seamounts, using a micronekton trawl (side length of body mesh: 40 mm, side length of cod‐end mesh: 10 mm) at 35 stations from 0 to 1, 113 m depth. A new maximum standard length for Bonapartia pedaliota and Ectreposebastes imus are also provided.